FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU OVER-CONFIDENCE INVESTOR SAHAM DI YOGYAKARTA - Kartini Kartini; Dwika Apriliani Setiawan (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2017)
This study aims to determine the factors that influence the behavior of investor overconfidence in Yogyakarta. This study uses questionnaire distributed to 100 randomly selected respondents. A total of 80 questionnaires were used, hile the other 20 were disqualified because of unallocated or incomplete answers. The data were processed using SPSS measuring devices stepwise regression. This research gets the result and overconfidence of investor is influenced by variables advice, while age, gender, experience, past performance and management qualifications not influence toward overconfidence investor